Graptolites from the Englewood Formation (Mississippian) of the Black Hills, South Dakota - Ruedemann, R.; Lochman , C. (Journal of Paleontology, 1942)
The description of three new species of Dictyonema from the basal shales of the Englewood formation of the Black Hills, South Dakota, places on record the second known occurrence of graptolites in rocks of Mississippian age in North America.
Keywords: paleontology